2016
DOI: 10.1088/0957-4484/27/42/425602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bovine serum albumin-protected high fluorescence Pt16-nanoclusters and their application to detect sulfide ions in solutions

Abstract: Highly fluorescent (quantum yield, QY = 17%) Pt16-nanoclusters (Pt16-NCs@BSA) have been prepared via a one-step ultrasonic-assistance method by using cheap and easily available ascorbic acid as reductant and bovine serum albumin (BSA) as a stabilizing agent in aqueous solution. The fluorescence properties of the Pt-NCs@BSA can be easily controlled by optimizing conditions, and the products are extremely stable and could be used for the detection of sulfide ions (S(2-)) in solutions as a specific luminescence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Special efforts are being addressed towards the synthesis of platinum NCs (PtNCs). PtNCs show lower toxicity than QDs [19] and templates such as proteins, DNA, polymers and dendrimers have been investigated for the synthesis of water soluble PtNCs [20][21][22][23][24]. However, major drawbacks of big scaffolds are the difficulties both to remove the remaining free templates from the NCs in solution and to isolate the NCs from the big scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Special efforts are being addressed towards the synthesis of platinum NCs (PtNCs). PtNCs show lower toxicity than QDs [19] and templates such as proteins, DNA, polymers and dendrimers have been investigated for the synthesis of water soluble PtNCs [20][21][22][23][24]. However, major drawbacks of big scaffolds are the difficulties both to remove the remaining free templates from the NCs in solution and to isolate the NCs from the big scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the small size and steric ChemistrySelect protection of Gd 2 O 3 by BSA, it could be safely utilized in the biological system and retained for longer. [29,40] The BSA protein is well known to serve as a template for controlled nucleation and grain growth of nanoclusters imparting colloidal stability, [41] and the commercially available ascorbic acid was used as a reductant, which is non-toxic and biodegradable [42] in nature. It has been observed that fluorescence intensity in longer wavelengths (green, red) increases (ESI-Figure S1) with incubation time (up to 72 hrs) due to the formation of a larger nanocluster, which is in good harmony with other published articles.…”
Section: Resultsmentioning
confidence: 99%
“…The intensities of binding energy for Au(0) and Au(I) reveal that their ratio in particles was 66.31 and 33.69%, respectively, confirming the predominance of Au(0), while that of Pt in NCs (Figure 5D) shows a strong peak at 72.8 eV for Pt 4f7/2 , which is assigned to Pt(I). 50 The results show that the binding energies of Au (Au 4f7/2 , 84.4 eV) and Pt (Pt 4f7/2 , 72.8 eV) in Au−PtNCs-GMP are obviously different from those of Au 4f7/2 (84.0 eV) 51 and Pt 4f7/2 (71.6 eV) in bulk, 50 respectively. Therefore, the modified electronic structures of metal enhance the catalytic properties of Au−PtNCs-GMP.…”
Section: Intrinsic Mechanism Of Optimized Au−ptncs-gmp For Tmb Oxidat...mentioning
confidence: 99%